Smart Partnership and Innovative Holistic Development Projects: A Case Study of Waqf Land of Nurul Islam Society - Shaik Abdullah Bin Hassan Mydin (Proceedings of AICS - Social Sciences, 2017)
Waqaf Land and Development under Nurul Islam Society is a smart partnership project and an innovative holistic development projects. The land will be used for developing madrasah, surau, multi-purpose hall, counselling centre, musafir accommodation, and also recreational sports. Total cost for the land and development is RM 15million. A 6 storey building will be erected on this land which boasts various facilities, Islamic educational programme and communal activities such as multipurpose hall, madrasah and surau, free clinic and community service centre, library and lodging for travellers. For this, Wakaf Land and Development of Nurul Islam Society wish to shoulder some responsibility in providing optimised spiritual retreat for those who seek to develop themselves, and as a platform for quality youth development programme. Some of the activities will include spiritual, emotional and physical enlightenment, which touches on our relationship with Allah, with mankind and teaches the youth to have visionary outlook. Such activities will also be an antidote to their addiction towards gadgets and gizmos, which is now becoming a serious disease. It is paramount for us to conquer this issue in order to groom them to be the nation’s future leaders. Thus this paper will be beneficial in the contexts of smart partnership and development of waqf land innovatively and creatively in the broader perspective in line with the spirit of waqf to maximize benefit for the betterment of ummah.